1998
DOI: 10.1046/j.1365-2567.1998.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of renin–angiotensin system inhibitors on pro‐ and anti‐inflammatory cytokine production

Abstract: SUMMARYThe balance between pro-and anti-inflammatory cytokines has been implicated in the pathogenesis of infectious and auto-immune diseases, and its modulation has been proposed as a potential therapeutic target. The results reported in the present study show that modulators of the reninangiotensin system, such as the angiotensin-converting enzyme (ACE )-inhibitor captopril and the angiotensin II receptor type I antagonist valsartan, have potent inhibitory effects on the lipopolysaccharide (LPS )-stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 24 publications
5
65
0
2
Order By: Relevance
“…5). Our results are in accordance with those showing that proinflammatory and anti-inflammatory cytokines secreted by human PBMCs are not affected by captopril administration (52). These results are also counter to those of other groups reporting that captopril enhances T cell function in their model systems (53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 91%
“…5). Our results are in accordance with those showing that proinflammatory and anti-inflammatory cytokines secreted by human PBMCs are not affected by captopril administration (52). These results are also counter to those of other groups reporting that captopril enhances T cell function in their model systems (53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 91%
“…There is also evidence to suggest that formation of Ang II may contribute to the loss of body tissue in mice bearing the MAC16 tumour, since imidapril attenuated the development of weight loss in this model. Ang II directly stimulates tumour necrosis factor-a (TNF-a) and interleukin-6 (IL-6) production in human peripheral monocytes and ACE inhibitors inhibit LPS-induced TNF-a production (Peeters et al, 1998). However, the activity of imidapril in the MAC16 model could not be explained by an effect on TNF-a or IL-6 production, since we have previously shown no involvement of these cytokines in the cachectic process in this model (Mulligan et al, 1992).…”
Section: Discussionmentioning
confidence: 91%
“…The benecial effects of ACE inhibitors have mainly been attributed to diminished cardiac workload by interference with the renin -angiotensin-aldosterone system. However, ACE inhibitors have subsequently been shown to possess anti-in ammatory properties (8) and it may be speculated that some of the bene cial effects of ACE inhibitors are conferred by such activities. For example, it was recently shown that reduced cardiac septum thickness after enalapril treatment in congestive heart failure patients was related to decreased inammation (9).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%